Bovine leukemia virus matrix-associated protein MA(p15): further processing and formation of a specific complex with the dimer of the 5'-terminal genomic RNA fragment. - Katoh, I (1991)
The retrovirus precursor protein has an arrangement of several characteristic domains with which it achieves selective and efficient packaging of the genome RNA during particle assembly. In this study, we analyzed the composition of the bovine leukemia virus (BLV) gag proteins and examined their RNA-binding properties in gel mobility shift assays, using various genomic RNA probes synthesized in vitro. Results obtained in amino acid sequence and composition analyses indicate that the matrix-associated protein MA(p15) is further processed by the BLV protease (PR) to generate MA(p10), a short peptide of seven amino acid residues, and p4. The gag precursor is now mapped as NH2-MA(p10)-p4-CA(p24)-NC(p12)-COOH. MA(p15) formed a specific complex with the dimer RNA of the U5-5' gag region presumed to contain the BLV packaging signal but not with other RNAs. The NH2-terminal cleavage product, MA(p10), bound all RNA fragments tested, while the COOH-terminal peptides with a sequence common to mammalian type C retroviruses had little affinity for RNA. The nucleocapsid protein NC(p12) bound to RNAs nonspecifically and randomly in the presence or absence of zinc ions. These results suggest a possible interaction of the NH2 terminus of the gag precursor with the 5' terminus of the genomic RNA in an early phase of particle assembly, when the conserved structure between the MA and CA domains might be involved.